2017
DOI: 10.1111/ejn.13633
|View full text |Cite
|
Sign up to set email alerts
|

Scheduled meal accelerates entrainment to a 6‐h phase advance by shifting central and peripheral oscillations in rats

Abstract: Travelling across several time zones requires a fast adjustment of the circadian system and the differential adjustment speeds of organs and systems results in what is commonly referred as jet lag. During this transitory state of circadian disruption, individuals feel discomfort, appetite loss, fatigue, disturbed sleep and deficient performance of multiple tasks. We have demonstrated that after a 6-h phase advance of the light-dark cycle (LD) scheduled food in phase with the new night onset can speed up re-ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 64 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…TRF also reduces the risk for compromised muscle function in flies held under continuous light and adds to a growing interest in adjusting mealtime as an effective approach to cope with shiftwork. In a rat model of jetlag or shiftwork, TRF aligns with the nocturnal active phase of the animal that rapidly re-entrains the peripheral circadian clocks 57 . This can reduce desynchronization between clocks in the neural and the peripheral tissues and may improve metabolic health.…”
Section: Discussionmentioning
confidence: 99%
“…TRF also reduces the risk for compromised muscle function in flies held under continuous light and adds to a growing interest in adjusting mealtime as an effective approach to cope with shiftwork. In a rat model of jetlag or shiftwork, TRF aligns with the nocturnal active phase of the animal that rapidly re-entrains the peripheral circadian clocks 57 . This can reduce desynchronization between clocks in the neural and the peripheral tissues and may improve metabolic health.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence place the DVC, including the AP and NTS, as an important hindbrain circadian timekeeping centre (Kaneko et al, 2009;Ubaldo-Reyes et al, 2017;Chrobok et al, 2020). Interestingly, in our previous study, we identified an area of the NTS adjacent to the AP in which circadian rhythmicity in the Per2 clock gene expression was sustained in ex vivo brain slices for up to a week in culture.…”
Section: Discussionmentioning
confidence: 69%
“…Since a brief light exposure (30 to 60 min of 200 lux light) at subjective night increases c-Fos expression selectively in the ventrolateral part of the SCN [ 8 , 16 ], light may be the causative to affect the SCN cells under jet lag conditions. Compared to c-fos expression in the SCN under jet lag conditions in rats [ 12 , 23 ], we found c-Fos positive cells in wider parts of the SCN, including its central area (See Fig. 1 , Fig.…”
Section: Discussionmentioning
confidence: 81%